Identifying Covid19 Impact on Peruvian Mental Health during Lockdonw using Social Network - Chire, Josimar (2021)
ABSTRACT The actual outbreak generated by SARS-CoV-2, presented a challenge to the governments because PublicS Health, Economy, and Society are different in every country so actions must fit considering these previous conditions. South America is a region with developing countries, limitations, problems and the pandemic highlighted them. Peru is a country with good initial policies to contain the pandemic, a lockdown started on March 15 and lasted more than 100 days. By consequence, people were forced to change daily activities and of course, social and mental problems started to grow. The actual study wants to identify the covid-19 impact on the Social Network, Twitter filtering posts related to the topic. The initial findings present a high interest in the topic during the first week and a decreasing pattern in the last weeks.